MENELADANI ETOS KERJA RASULULLAH SAW - Zaini, Ahmad (Universitas Islam Negeri Sunan Kudus, 2015)
Human beings are given freedom to seek provision in accordance with applicable law and in a way that is fair. This is one of the obligations of human rights in Islam. Allah SWT. has established through the ordinance of him that any kind of work that run based on the principles of Koranic will never make one rich in a brief period of time. In the view of Islam, work not just as the pusher man to maintain their existence in life, but is the basis of all things. People began to work has been started since the Prophet Adam and his seedinhabiting the earth. She has been at pains to and hard to meet the needs of his life, while in paradise Adam got without the feeling of weariness and fatigue. So also the Prophet (saas. Is a hard worker through the efforts of trade he do when reselling merchandise owned by Siti Khadijah. The Messenger of Allah alone always tries to hit to all his people so that they have a high work ethos. Efforts done by Mohammed. So that the people of Islam have a high working ethos was not only shown through several hadith that he sabdakan, but also shown itself by Muhammad through a more real action. Muhammad showed himself as a person that ethnic high work, not easy to surrender, hard worker and reluctant to freaks who sit.